The influence of social media marketing and service quality on customer satisfaction as an intervening variable towards the purchase decision of chest freezer products at PT. Royal Sutan Agung - Dewi Ervinna; Yusuf Ronny Edward; Yeni Ariesa; Nindya Dewi Rizka Sari (Privietlab, 2023)
The objective of this research is to find out the influence of social media marketing and service quality towards purchase decision through customer satisfaction as intervening variable at Royal Sutan Agung LLC., Medan. The number of samples used in this research are 78 customers of Royal Sutan Agung LLC., Medan. The sampling technique that is used in this research is the convenience sampling method. Location of the research is located at Royal Sutan Agung LLC., Medan. The data collection method that is used is by using questionnaires that has been tested previously in validity and reliability. Data analysis method that is used by using path analysis. The results of this research are social media marketing has positive and significant influence towards purchase decision, service quality has positive and significant influence towards purchase decision, social media marketing has positive and significant influence towards customer satisfaction, service quality has positive and significant influence towards customer satisfaction, customer satisfaction has positive and significant influence towards purchase decision, social media marketing has an indirect positive and significant influence towards purchase decision through customer satisfaction and service quality has an indirect positive and significant influence towards purchase decision through customer satisfaction at Royal Sutan Agung LLC., Medan.